Injectable hyaluronic acid-based antibacterial hydrogel adorned with biogenically synthesized AgNPs-decorated multi-walled carbon nanotubes - Makvandi, Pooyan; Ashrafizadeh, Milad; Ghomi, Matineh; Najafi, Masoud; Hossein, Hamid Heydari Sheikh; Zarrabi, Ali; Mattoli, Virgilio; Varma, Rajender S (Progress in biomaterials, 2021)
Injectable materials have shown great potential in tissue engineering applications. However, bacterial infection is one of the main challenges in using these materials in the field of regenerative medicine. In this study, biogenically synthesized silver nanoparticle-decorated multi-walled carbon nanotubes (Ag/MWCNTs) were deployed for adorning biogenic-derived AgNPs which were subsequently used in the preparation of thermosensitive hydrogels based on hyaluronic acid encompassing these green-synthesized NPs. The antibacterial capacity of AgNPs decorated on MWCNTs synthesized through Camellia sinensis extract in an organic solvent-free medium displayed a superior activity by inhibiting the growth of Gram-negative (E. coli and Klebsiella) and Gram-positive (S. aureus and E. faecalis). The injectable hydrogel nanocomposites demonstrated good mechanical properties, as well. The thermosensitive hyaluronic acid-based hydrogels also exhibited Tgel below the body temperature, indicating the transition from liquid-like behavior to elastic gel-like behavior. Such a promising injectable nanocomposite could be applied as liquid, pomade, or ointment to enter wound cavities or bone defects and subsequently its transition in situ to gel form at human body temperature bodes well for their immense potential application in the biomedical sector.
Keywords: Green synthesis; Injectable nanocomposite; Nanomedicine; Camellia sinensis; Thermosensitive hydrogels; Ag NPs; Antibacterial